Baseline Survey for Reproductive Disorders in Indigenous Dairy Animals Reared by Marginal Farmers in Three Districtsof Punjab - Honparkhe, Mrigank; Kumar, Ajeet; Singhal, Sumit; Bisla, Amarjeet; Singh Brar, Parkash; Singh Ghuman , Sarvpreet (The Indian Journal of Animal Reproduction, 2025)
The attainment of maximum production potential from an animal envisages one calf crop per year. However, various  reproductive problems are responsible for increasing the inter-calving period for more than 15 months even at the well  managed dairy farms. Most of the dairy animals in India as well as in Punjab are reared by small and marginal farmers  so, this study was aimed at to prepare baseline data of major reproductive problems in the indigenous dairy animals in  three districts (Ludhiana, Bathinda and Tarn taran) of Punjab. A total of 127 villages were covered for completing 3000  households (1000 per district) based on a predesigned questionnaire. It was observed that buffaloes were more reared  by all the small and marginal farmers of three districts than indigenous cattle. The average number of total cattle, total  buffaloes, adult buffaloes, buffalo heifers as well as total livestock per household varied significantly (p
Keywords: Anestrus; Buffalo; Delayed puberty; Indigenous cattle; Repeat breeding